Metacognition Perceived in the Education and English Language Education : A Systematic Literature Review - Bernadeta Setyaningsih; Sri Sumarni2; Darmahusni Darmahusni (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Metacognition as a process of thinking is essential in all areas of education and life since it requires thought on one's current position, future goals, workable solutions, and outcomes. This study aimed to investigate how metacognition was perceived in Education and English Language Education. A systematic review was conducted to explore studies presenting the perceived metacognition in both areas. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2020 standards were applied to ensure the systematic analysis of the selected papers. From two databases, Publish or Perish and Google Scholar a total of 11 peer-reviewed journal publications from the years 2018 to 2023 were accessed. From the articles reviewed, the concept of metacognition was perceived as ‘understanding one's thinking; ‘awareness of own thinking’; ‘thinking about thinking’; ‘self-regulation of own thinking’; ‘awareness and understanding of own thinking’ in education; while in English Language Education, it was perceived as metacognitive knowledge; metacognitive awareness; metacognitive experiences; metacognitive strategies; cognition and others (self-regulation, autonomous learning, higher-order skills, executive skills, metacomponents, metamemory). In addition to attempting to investigate how metacognition was regarded, this study suggested educators who need to redesign relevant knowledge, skills, and character qualities for the twenty-first century learning, they have to facilitate students engage in self-reflection, learn about their learning, use prospective actions and techniques that assist transferring competences across disciplines, and learn how to change their learning and behavior based on their goals.